Bharathanatyam - It’s Technique, Margam and Jewellery: A Tantric Perspective - Poornima Rajini; Susheela S. N. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
Any Indian classical performing art is a medium through which one can express a philosophy of life which aims to transcend oneself towards a higher plane and achieve bliss through spiritual expression for the performer and the audience. “All Indian classical dances are a combination of body movements and facial expressions perfectly synchronized to represent a given context, through the perfect vehicle, the human body. Though it is the body that moves, it is man’s inner consciousness or soul that directs his movements. This results in a harmonistic dance form that combines music, rhythm, and movement, all of which cater to the command of man’s inner feelings. The philosophy of art aims to manifest the inner self of man which is divine in nature in a spiritual country like India, where the realization of consciousness or spirit has been the supreme goal of life, it is not a wonder that dance became a form of sadhana.” Tantra - Tantrayate vistāryate jnanam anena’ - i.e., by which knowledge is spread or developed. When art-forms take their being from fundamental cosmic principles, they participate in the essential structure of the universe and contain a natural symbolism to which unsophisticated human beings respond instinctively, unconsciously” (Boner 6, 7).